Oliver Cromwell, iconoclasm and Ely cathedral. Issue 236 (13th April 2014) - Hart, Graham
Abstract: A previously neglected source casts new light on Cromwell's interruption of evening prayer in Ely cathedral in January 1644, which has often been cited as evidence of his religious radicalism. Joseph Beaumont's eyewitness account shows that Cromwell intervened only after his soldiers had taken the initiative. Beaumont also provides new evidence of the soldiers' iconoclasm in the cathedral, which was followed by an attack on the prayer book throughout the Isle of Ely. This source supports the view that Cromwell did not personally commit iconoclasm, but does nothing to dispel doubt about his attitude towards direct action by his troops.